2012
DOI: 10.1590/s2176-94512012000500018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of facial profile changes in patients treated with maxillary premolar extractions

Abstract: Objective: Evaluate the facial profile changes of orthodontic treatment with extraction of two upper first premolars, from the perspective of orthodontists, dentists and lay people. Methods: Facial profiles of radiographs taken before and after treatment of 70 patients with Class II, division 1 malocclusion were traced. The silhouettes of the 70 patients were randomly assembled in an album with, being two profiles on each sheet of the same patient. Then, 30 orthodontists, 30 dentists and 30 lay people chose th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
2
12
1
1
Order By: Relevance
“…The results demon st rated a stat ist ically significant difference (p=0.003) in the opinion of lay individuals and orthodontists, even though both evaluated the posttreatment profile as more pleasant (Table 4). This corroborates the study by Almeida-Pedrin et al 20 , who analyzed the facial profile changes promoted by orthodontic treatment with the extraction of two maxillary first premolars, and revealed that 83 out of 90 examiners preferred the posttreatment profile.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results demon st rated a stat ist ically significant difference (p=0.003) in the opinion of lay individuals and orthodontists, even though both evaluated the posttreatment profile as more pleasant (Table 4). This corroborates the study by Almeida-Pedrin et al 20 , who analyzed the facial profile changes promoted by orthodontic treatment with the extraction of two maxillary first premolars, and revealed that 83 out of 90 examiners preferred the posttreatment profile.…”
Section: Discussionsupporting
confidence: 91%
“…14,17,18 However, aspects that influence examiners' perceptions of facial attractiveness may be eliminated by using profile silhouettes. 15,19,20,21,22 The concept that orthodontic treatment by extraction of premolars damages facial profile esthetics often keeps the orthodontist back from choosing this option in devising the treatment planning. In this respect, over the years, orthodontists have been investigating the relationship between facial profile esthetics and orthodontic treatment by tooth extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers noted that the premolar extraction treatment might not result in a less pleasant facial profile than a nonextraction protocol does, as long as the treatment option is adequate. This result was also confirmed by another study 15 assessing the facial impact of orthodontic treatment with the extraction of the upper premolars. They concluded that the therapeutic effect of this treatment, when properly indicated, would be always positive.…”
Section: Resultssupporting
confidence: 71%
“…However, once an intervention is required, it is necessary that the professional takes extreme care for the preservation and accentuation of the pleasant characteristics. Lately, the laypersons' perception regarding esthetic appearance has been attributed as much importance as that of the professionals [15][16] .…”
Section: Resultsmentioning
confidence: 99%